MALDI-imaging mass spectrometry - An emerging technique in plant biology - Kaspar, Stephanie; Peukert, Manuela; Svatos, Ales; Matros, Andrea; Mock, Hans-Peter (Proteomics (Weinheim), 2011)
Recent advances in instrumentation and sample preparation have facilitated the mass spectrometric (MS) imaging of a large variety of biological molecules from small metabolites to large proteins. The technique can be applied at both the tissue and the single‐cell level, and provides information regarding the spatial distribution of specific molecules. Nevertheless, the use of MS imaging in plant science remains far from routine, and there is still a need to adapt protocols to suit specific tissues. We present an overview of MALDI‐imaging MS (MSI) technology and its use for the analysis of plant tissue. Recent methodological developments have been summarized, and the major challenges involved in using MALDI‐MSI, including sample preparation, the analysis of metabolites and peptides, and strategies for data evaluation are all discussed. Some attention is given to the identification of differentially distributed compounds. To date, the use of MALDI‐MSI in plant research has been limited. Examples include leaf surface metabolite maps, the characterization of soluble metabolite translocation in planta, and the profiling of protein/metabolite patterns in cereal grain cross‐sections. Improvements to both sample preparation strategies and analytical platforms (aimed at both spectrum acquisition and post‐acquisition analysis) will enhance the relevance of MALDI‐MSI technology in plant research.